2016
DOI: 10.1177/0009922816635808
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation and Home Monitor Use in Late Preterm to Term Infants With Apnea, Bradycardia, and Desaturations

Abstract: Apnea, bradycardia, and oxygen desaturation events are a common in neonatal intensive care units, with relevant literature to date largely focusing on very low birth weight and extremely low birth weight infants. We conducted a retrospective review of infants born at ≥34 weeks gestational age at 2 tertiary neonatal intensive care units in Boston, MA, between January 2009 and December 2013. Our objectives included (1) describing the diagnostic evaluations performed in late preterm to term infants with discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
1
1
3
Order By: Relevance
“…American Academy of Pediatrics’ clinical report states that CR monitor may be prescribed for some preterm infants with an unusually prolonged course of recurrent extreme apnea, and such monitoring should be discontinued in most infants after 43 weeks. In contrast the time of discontinuation of CR monitor in our subjects was 46 weeks and thus not consistent with recent recommendation by the AAP [ 4 , 20 ]. Thus there is a need to standardize the reporting of polysomnography studies and clear indications are needed for use of home CR monitoring since they both add to the cost of patient care with no clear demonstrable benefit to the patients.…”
Section: Discussioncontrasting
confidence: 90%
“…American Academy of Pediatrics’ clinical report states that CR monitor may be prescribed for some preterm infants with an unusually prolonged course of recurrent extreme apnea, and such monitoring should be discontinued in most infants after 43 weeks. In contrast the time of discontinuation of CR monitor in our subjects was 46 weeks and thus not consistent with recent recommendation by the AAP [ 4 , 20 ]. Thus there is a need to standardize the reporting of polysomnography studies and clear indications are needed for use of home CR monitoring since they both add to the cost of patient care with no clear demonstrable benefit to the patients.…”
Section: Discussioncontrasting
confidence: 90%
“…While the literature on the cause of apnea in term infants and the yield of the diagnostic workup is extensive, there is little knowledge about its longterm outcome (3,13) . The study of Levin et al (2) demonstrated that apnea is associated with higher length of stay and cost in the newborn hospitalization, with variation in hospital practice.…”
Section: Discussionmentioning
confidence: 99%
“…На долю апноэ недоношенных приходится максимальная частота встречаемости апноэ как симптомокомплекса, что предполагает особую настороженность в отношении новорожденных групп риска, подверженных развитию данного заболевания с вероятностью 80%, которыми являются дети с очень низкой (ОНМТ), экстремально низкой массой тела (ЭНМТ), а также с ГВ <32 нед [14]. [4,[15][16][17][18][19]  ГВ <32 нед.…”
Section: диагностика заболевания или состояния (группы заболеваний ил...unclassified
“… Недоношенным новорожденным с повторяющимися и/или тяжелыми апноэ рекомендуется проведение рентгенографии либо ультразвукового исследования (УЗИ) легких для исключения заболеваний и патологических процессов в легочной ткани [14,33,[71][72][73][74][75][76][77][78][79]. [80,81].…”
Section: уровень убедительности рекомендаций B (уровень достоверности...unclassified